Implementasi Model Peta Konsep dalam Peningkatan Kemampuan Bercerita Siswa SDN 69 Kota Banda Aceh - Mustafa Mustafa (Tadabbur: Jurnal Peradaban Islam, 2020)
Implementing the concept map learning model is one of the efforts to improve the ability of grade fives tudents in telling the Prophets stories at SDN (public elementary school) 69 in Banda Aceh. In this study, the concerns were on the teacher’s activity in the implementation of the concept map learning model, the students’ activity in the concept map learning model, and the improvement of the students' story telling skills within the concept map learning model. The subject of this study was the improvement of storytelling skills by using the concept map model. This study employed a three-cycle classroom action research, in which each cycle consisted of planning, implementation, observation, and reflection. Data were collected by oral test and observation, and analyzed quantitatively.The results of the study showed that there was an increase in the students’ storytelling test results, including prior to the intervention, and in all three cycles. The classical average score reached 60.62 in cycle I,63.87 incycle II, and increased to 75.87 in cycle III. The results achieved in cycle III have fulfilled the average score target of 73, meaning that thestudents’ ability in telling story had improved after using the concept map model. This improvement also suggested that the concept map learning model was successful, as it was further reflected by the increase of the teacher’s and the students’ activities. Theobservation results revealed that the teacher’s activity in cycle I was 67.5%, rose to 75% in cycleII, and to 92.5% in cycle III. In terms of the students’ activity, in cycle I the proportion was 59.37%, and then rose respectively to 74.47% in cycle II, and 85.97% in cycle III.